Fast drosophila enterocyte regrowth after infection involves a reverse metabolic flux driven by an amino acid transporter - Catherine Socha; Inês S. Pais; Kwang-Zin Lee; Jiyong Liu; Samuel Liégeois; Matthieu Lestradet; Dominique Ferrandon (iScience, 2023)
Summary: Upon exposure to a bacterial pore-forming toxin, enterocytes rapidly purge their apical cytoplasm into the gut lumen, resulting in a thin intestinal epithelium. The enterocytes regain their original shape and thickness within 16 h after the ingestion of the bacteria. Here, we show that the regrowth of Drosophila enterocytes entails an inversion of metabolic fluxes from the organism back toward the intestine. We identify a proton-assisted transporter, Arcus, that is required for the reverse absorption of amino acids and the timely recovery of the intestinal epithelium. Arcus is required for a peak of amino acids appearing in the hemolymph shortly after infection. The regrowth of enterocytes involves the insulin signaling pathway and Myc. The purge decreases Myc mRNA levels, which subsequently remain at low levels in the arcus mutant. Interestingly, the action of arcus and Myc in the intestinal epithelium is not cell-autonomous, suggesting amino acid fluxes within the intestinal epithelium.